The Seduction of Speech: Building the Female Character in (Musika Sofiah) By Lutfiah Al-Dulaimi - Fawzi Muhammad Ali Wasmi, Haider (International Journal of Psychosocial Rehabilitation, 2020)
(Sufi music) texts resort to a different kind of bet, as they do not reproduce the female, but rather create a structure for the female personality, based on sabotaging the structure of the stuttering memory, and creating counter structures that are based on the narration, through interviews with the structure of the past/present, female robbery / Positive, within the structure of (time-negation) and thus the narrative game practiced by the text is evident through the relationships of its elements and the patterns of its structure, in showing a textual structure of the female is the structure of heterogeneity, as it penetrated in its reality and daily, to differ in its manifestation of the text.